Intradialytic exercise and postural control in patients with chronic kidney disease undergoing hemodialysis - Carletti, Carla Oliveira; Rosa, Clara Suemi Da Costa; Souza, Giovana Damasceno E; Ramirez, Ariane Pereira; Daibem, Célio Guilherme Lombardi; Monteiro, Henrique Luiz (Pontifícia Universidade Católica do Paraná, 2017)
AbstractIntroduction: Exercise promotes physiological improvements that reflect better quality of life and survival among chronic kidney disease patients. However, little is known about the effect of exercise on postural control of hemodialysis patients.Objective: To evaluate the effect of intradialytic aerobic exercise on postural balance in patients on hemodialysis.Methods: a pilot study with seven individuals was conducted at the Hemodialysis Center of Bauru State Hospital. The Berg Balance Scale evaluated balance and postural balance was evaluated by the force platform Advance Mechanical Technology Inc. (AMTI - AccuGait). Trunk mean sway amplitude in the anterior-posterior (AP) and medial-lateral (ML) directions and mean velocity in the AP and ML directions were assessed. Secondary outcomes about functional capacity and body composition (DEXA) were evaluated. The aerobic exercise was performed with a ergometric bicycle during the first two hours of hemodialysis session for 50-60 minutes (BORG >12), three times a week for 12-weeks.Results: Four men and three women, 52.86 ± 11.08 years, participated in the study. There was no difference between pre and post-test of postural balance outcomes. Although the results were not statistically significant, except for the lean body mass and leg lean mass, the presented pilot study suggests improved functional balance and lower limb strength.Conclusion: The 12-weeks of aerobic exercise protocol during hemodialysis despite inducing gains in lean body mass and leg lean mass, was not able to promote improvements in postural control of chronic renal failure patients on hemodialysis.

ResumoIntrodução: O exercício promove benefícios fisiológicos que reflete em melhor qualidade de vida e sobrevida do doente renal crônico. Contudo, pouco se sabe sobre o efeito do exercício físico sobre o equilíbrio postural destes pacientes em tratamento de hemodiálise.Objetivo: Avaliar o efeito do exercício intradialítico sobre o equilíbrio postural de pacientes renais crônicos submetidos a hemodiálise.Métodos: Sete indivíduos renais crônicos provenientes do Centro de Hemodiálise do Hospital Estadual de Bauru. O equilíbrio foi avaliado pela escala de equilíbrio de Berg e o equilíbrio postural por meio da plataforma de força (AMTI - AccuGait). Para o equilíbrio postural foram consideradas as variáveis amplitude média e velocidade de deslocamento médio ântero-posterior e médio-lateral do centro de pressão. Informações secundárias sobre capacidade funcional e composição corporal (DEXA) também foram avaliadas. O exercício aeróbio foi realizado por 50-60 minutos nas primeiras duas horas da sessão de hemodiálise, três vezes na semana, durante 12 semanas.Resultado: Quatro homens e três mulheres com 52,86 ± 11,08 anos participaram do estudo. Os momentos pré e pós exercício não apresentaram diferença estatisticamente significativa (p > 0,05) para as variáveis do equilíbrio postural. Contudo, houve ganho massa magra total e de perna. Os resultados sugerem também melhora do equilíbrio através da escala de Berg e força de membros inferiores, contudo sem significância estatística.Conclusão: O protocolo de doze semanas de exercício aeróbio durante a hemodiálise apesar de promover ganhos na massa magra total e de membros inferiores, não foi capaz de promover melhoras no controle postural de doentes renais crônicos em hemodiálise.
Exercício intradialítico e controle postural de doentes renais crônicos em hemodiálise
Keywords: Postural Balance; Chronic Kidney Disease; Hemodialysis; Rehabilitation; Equilíbrio Postural; Doença Renal Crônica; Hemodiálise; Reabilitação